Financial integration in East Asia: Past, present and possible futures - Inderjit N. Kaur; Nirvikar Singh (University of California, Economics Department, 2013)
This paper reviews the East Asian experience with financial integration, how economies in the region have responded to shocks, and what they may do to continue to thrive in the future. It discusses openness to capital flows as a key aspect of financial integration, briefly considering the theoretical underpinnings and empirical evidence for the benefits of openness. It then examines the East Asian experience with the two financial crises that have affected the region, and how the two episodes have differed. It concludes by considering policy options for the future, including regulatory reform and coordination, and various possible risk management policies and institutions. The analysis illustrates differences in patterns of financial development for the three largest economies of the region (China, Japan and South Korea) and discusses implications for financial integration efforts.
Keywords: F36; F42; F62; O16; 330; financial integration; financial development; financial crises; trilemma; monetary union; risk management